PEMANFAATAN TENUN ATBM SUTRA FABRIKASI KABUPATEN PASURUAN PADA WOMEN’S WEAR SUSTAINABLE FASHION UNTUK PASAR AUSTRALIA - Janet Rine Teowarang; Krishna Hutama; Yan Yan Sunarya (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2023)
Abstract Indonesia's fashion and textile industry is now trying to recover from the COVID-19 pandemic, which has significantly affected and stopped the productivity of eri silk farmers. In 2021, supplies of eri silk fiber began to be regained again through the KUPU Sutra organization from fundraising by Lenzing and MSME KaIND. However, the supply of eri silk fiber requires a definite sustainability cycle in order that eri silk farmers and handloom weaving artisans have good job stability by supporting their productivity. Women's wear sustainable fashion designed by fashion brand Allegra Jane in collaboration with the Australian fashion designer to be exhibited in Brisbane to introduce Pasuruan Regency handloom fabrication silk textile to the Australian market. This research is experimental-based research using an experimental design approach and experimental fashion. This research aims to utilize Pasuruan Regency handloom fabrication silk textile progressed into sustainable women's wear products with the theme 'Pasuruan Regency Fabrication Silk Within Fashion.' Keywords: Pasuruan Regency, women’s wear sustainable fashion, peace silk, fabrication silk, Australia market Abstrak Industri fashion dan tekstil di Indonesia kini berupaya bangkit dari pandemi COVID-19 yang memberikan dampak cukup besar, termasuk produktivitas petani yang membudidayakan ulat sutra eri juga sempat terhenti. Tahun 2021 persediaan serat sutra eri mulai kembali terkumpul melalui Koperasi KUPU Sutra karena penggalangan dana yang dilaksanakan oleh Lenzing dan UMKM KaIND. Namun, persediaan serat sutra eri memerlukan siklus keberlanjutan yang pasti, agar para petani sutra eri dan artisan tenun ATBM mempunyai stabilitas kerja baik dengan mendukung produktivitas mereka. Women’s wear sustainable fashion didesain oleh brand fashion Allegra Jane berkolaborasi dengan fashion desainer Australia untuk dipamerkan di kota Brisbane dengan tujuan mengenalkan tenun ATBM sutra fabrikasi Kabupaten Pasuruan untuk pasar Australia. Penelitian ini adalah experimental-based research yaitu dengan experimental design approach dan experimental fashion. Pelaksanaan penelitian ini bertujuan memanfaatkan tenun ATBM sutra fabrikasi Kabupaten Pasuruan yang diolah menjadi produk women’s wear sustainable fashion dengan tema ‘Pasuruan Regency Fabrication Silk Within Fashion’. Kata kunci: Pasuruan Regency, women’s wear sustainable fashion, peace silk, fabrication silk, pasar Australia